Guideline on peri-operative glycemic control for adult patient with diabetic mellitus: Resource limited areas. (2017) - Berhe, Yophtahe Woldegerima; Gebregzi, Amare Hailekiros; Endalew, Nigussie Simeneh
Abstract: Background: Poor glucose control/Hyperglycemia is associated with perioperative complications. Optimal evidence-based perioperative blood glucose control in patients undergoing surgical procedures remains controversial. There are different controversial approaches on glycemic control based on variety of evidences. So it is important to design and developed protocol to provide safe perioperative care for diabetic patients that align with our clinical setup. The objective of this guideline was to improve care provision regarding glucose control in diabetic patients during the Perioperative period. Methods: PubMed through HINARI, Google Scholars and other search engines were used to find high level evidences that help to draw appropriate conclusions. Discussion: Comparing conventional and intensive glucose control, even though, intensive approach was found associated with reduced complication rates, recent large scale studies concluded no difference in complication rates, organ failure, and ventilator support requirements. The intensive approach, even found associated with more episodes of hypoglycemia and higher delayed mortality rates. Regarding insulin administration modalities, continuous infusion was found to help stable glycemic control, reduce 30-days re-admission, and postoperative infections. Conclusion: Diabetic patients frequently come to operation theatre for wide range of procedures. One of the challenging aspects of peri-operative care in these patient groups is appropriate glycemic control. The management should be guided by the pre-operative glycemic control, type and duration of the operation (minor or major) and functional reserve of patients. The guideline has been summarized in flow chart form to simplify its application. Highlights: To improve care provision regarding glucose control in diabetic patients. Intensive glucose control decreased overall post-operative complications. Continuous insulin infusion associated with significant reduction in wound infection. Continuous insulin infusion is more effective in controlling blood glucose. Perioperative glycemic control, intensive insulin therapy, conventional insulin therapy.